BRIDGING THE GAP BETWEEN THE TOURISM INDUSTRY AND TERTIARY INSTITUTIONS OFFERING TOURISM IN GHANA: A CASE STUDY OF CAPE COAST - Raphael Avornyo (European Scientific Journal, ESJ, 2014)
Ghana, as a country, has been trying to promote tourism with the aim of achieving rapid socio-economic development objectives, including employment creation, improvements in standard of living, diversification of economies and making the industry one of the main foreign exchange earners for the country. One way of realising these, is to ascertain the benefits that tertiary institutions and tourism establishments derive from the tourist activities and the challenges that they face. This paper, therefore, aims at finding out the level of collaboration between the tourism industry and educational institutions offering tourism and hospitality management, the benefits that they derive and the challenges they face in trying to collaborate with one another and recommendations for improving the level of collaboration. Data for the study were collected using an interview guide from five Lecturers and 20 management and staff from hotels, restaurants, tour operations and attractions. The study employs the qualitative method of analysis. The results of the study show that the educational institutions and the tourism industry both derived some benefits from some sort of collaboration. However, they were faced with challenges such as inadequate practical knowledge of graduates from the academic institutions, lack of regular and in-depth communication between the industry and the academic institutions. This paper recommends a partnerships approach aimed at surmounting the challenges and fostering closer collaboration.